Real-time three-dimensional transesophageal echocardiography to predict artificial chordae length for mitral valve repair - Huang, Huan-lei (BioMed Central, 2013)
BACKGROUND: Artificial chordae replacement is an effective technique for mitral valve repair, however, it is difficult to accurately determine the length of artificial chordae. This study aimed to assess the reliability and accuracy of real-time three-dimensional transesophageal echocardiography (TEE) to predict the length of artificial chordae preoperatively. METHODS: From December 2008 to December 2010, 48 patients with severe mitral regurgitation successfully underwent mitral valve repair using artificial chordae replacement. The patients were divided into a TEE pre-measurement group (n = 26) and a direct measurement group (n = 22), according to the method used to determine the length of artificial chordae. Cardiopulmonary bypass time, aortic cross-clamp time, and the recurrence rate of moderate or severe mitral regurgitation were compared between the two groups. RESULTS: There were no operative deaths in either group. The mean cardiopulmonary bypass time was 113.0 ± 18.7 min and 127.0 ± 28.9 min (p < 0.05), and the aortic cross-clamp time was 70.0 ± 16.6 min and 86.0 ± 20.7 min (p < 0.05) in the TEE pre-measurement group and direct measurement group, respectively. The difference between the pre-measured artificial chordal length and actual constructed artificial chordal length was not significant in the TEE pre-measurement group (p > 0.05). Although the difference in the incidence of moderate or severe mitral regurgitation between the two groups was not significant (p > 0.05), the incidence in the TEE pre-measurement group (3.8%) was lower than that in the direct measurement group (18.2%). CONCLUSIONS: Real-time three-dimensional transesophageal echocardiography can accurately predict the length of artificial chordae required for mitral valve repair, and shortens cardiopulmonary bypass time and aortic cross-clamp time while improving the results of mitral valve repair.